Mildly dysplastic oral lesions with optically-detectable abnormalities share genetic similarities with severely dysplastic lesions. (December 2022) - Brenes, David R.; Nipper, Allison J.; Tan, Melody T.; Gleber-Netto, Frederico O.; Schwarz, Richard A.; Pickering, Curtis R.; Williams, Michelle D.; Vigneswaran, Nadarajah; Gillenwater, Ann M.; Sikora, Andrew G.; Richards-Kortum, Rebecca R.
Graphical abstract: Highlights: It is a challenge to assess risk of progression of oral lesions with mild dysplasia. Optical imaging can aid in early detection of oral lesions with severe dysplasia. We compared optical markers and gene expression for mild and severe oral dysplasia. Optical marker positive mild dysplasia is genetically similar to severe dysplasia. Abstract: Objective: Optical imaging studies of oral premalignant lesions have shown that optical markers, including loss of autofluorescence and altered morphology of epithelial cell nuclei, are predictive of high-grade pathology. While these optical markers are consistently positive in lesions with moderate/severe dysplasia or cancer, they are positive only in a subset of lesions with mild dysplasia. This study compared the gene expression profiles of lesions with mild dysplasia (stratified by optical marker status) to lesions with severe dysplasia and without dysplasia. Materials and methods: Forty oral lesions imaged in patients undergoing oral surgery were analyzed: nine without dysplasia, nine with severe dysplasia, and 22 with mild dysplasia. Samples were submitted for high throughput gene expression analysis. Results: The analysis revealed 116 genes differentially expressed among sites without dysplasia and sites with severe dysplasia; 50 were correlated with an optical marker quantifying altered nuclear morphology. Ten of 11 sites with mild dysplasia and positive optical markers (91%) had gene expression similar to sites with severe dysplasia. Nine of 11 sites with mild dysplasia and negative optical markers (82%) had similar gene expression as sites without dysplasia. Conclusion: This study suggests that optical imaging may help identify patients with mild dysplasia who require more intensive clinical follow-up. If validated, this would represent a significant advance in patient care for patients with oral premalignant lesions.